The Development and Validation of the Artificial Intelligence Literacy Scale for Chinese College Students (AILS-CCS) - Shuai Ma; Zhenzhen Chen (IEEE Access, 2024)
In the context of rapid advancements in artificial intelligence (AI), enhancing AI literacy among college students is crucial for promoting the sustainable development of higher education. It is imperative to strengthen the assessment and training of AI literacy among college students. however, there is currently a lack of effective tools for evaluating AI literacy in students from developing countries. Therefore, based on previous literature and the Chinese context, this study developed and validated an Artificial Intelligence Literacy Scale for Chinese College Students (AILS-CCS). After developing the initial framework, this study collected survey data (N =546) through random sampling. Following the execution of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), the final validated AILS-CCS emerged as a theoretically and empirically consistent tool, consisting of 15 items across four dimensions: Awareness, Usage, Evaluation, and Ethics. This tool holds significant importance for the assessment and training of AI literacy among college students in China and other developing countries globally.